1999
DOI: 10.1073/pnas.96.18.10512
|View full text |Cite
|
Sign up to set email alerts
|

Sugars modulate an unusual mode of control of the cell-wall invertase gene ( Incw 1) through its 3′ untranslated region in a cell suspension culture of maize

Abstract: We show here that a cell-wall invertase encoded by the Incw1 gene is regulated at both the transcriptional and posttranscriptional levels by sugars in a heterotrophic cell suspension culture of maize. The Incw1 gene encoded two transcripts: Incw1-S (small) and Incw1-L (large); the size variation was attributable to different lengths in the 3 untranslated region. Both metabolizable and nonmetabolizable sugars induced Incw1-L RNA apparently by default. However, only the metabolizable sugars, sucrose and D-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…In addition, sugar sensing also affects gene expression posttranscriptionally by changing mRNA stability, translation, or protein stability (Chan and Yu, 1998;Rook et al, 1998;Cheng et al, 1999;Yanagisawa et al, 2003;Wiese et al, 2004). Interestingly, the regulation of the maize cell wallbound invertase Incw-1 is included among these examples (Cheng et al, 1999). Incw-1 is expressed in maize TCs, and we reported the association between metabolizable sugars and the increase in the steady state abundance of functional Incw-1 RNA.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, sugar sensing also affects gene expression posttranscriptionally by changing mRNA stability, translation, or protein stability (Chan and Yu, 1998;Rook et al, 1998;Cheng et al, 1999;Yanagisawa et al, 2003;Wiese et al, 2004). Interestingly, the regulation of the maize cell wallbound invertase Incw-1 is included among these examples (Cheng et al, 1999). Incw-1 is expressed in maize TCs, and we reported the association between metabolizable sugars and the increase in the steady state abundance of functional Incw-1 RNA.…”
Section: Discussionmentioning
confidence: 76%
“…Changes in sugar concentration cause induction or repression of gene transcription, providing a mechanism for interaction between sink and source tissues for carbohydrate metabolism (Koch, 1996). In addition, sugar sensing also affects gene expression posttranscriptionally by changing mRNA stability, translation, or protein stability (Chan and Yu, 1998;Rook et al, 1998;Cheng et al, 1999;Yanagisawa et al, 2003;Wiese et al, 2004). Interestingly, the regulation of the maize cell wallbound invertase Incw-1 is included among these examples (Cheng et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Rice suspension cell culture, which is readily amenable to exogenous metabolic manipulations, was used as a model system for these studies. The usefulness of this type of cell culture in such studies is well documented (Graham et al, 1994;Ehness et al, 1997;Cheng et al, 1999;Yu, 1999a). In the present studies, some growth-and stress-related genes upand down-regulated by Suc, respectively, were identified and found to be differentially and coordinately regulated by Suc, and the regulation involves control of both transcription rate and mRNA stability.…”
mentioning
confidence: 99%
“…Studies on ␣Amy3 mRNA have also identified essential sequences in its 3Ј-untranslated region (3Ј-UTR) that control sugar-dependent mRNA stability Yu, 1998a, 1998b). The 3Ј-UTR of a cell wall invertase gene (Incw1) recently was shown to be involved in translational control of Incw1 by sugars in cultured maize suspension cells (Cheng et al, 1999).…”
mentioning
confidence: 99%
“…However, ABA and sucrose increased the transcript levels of Incw1, but the induction of ABA combined with sucrose showed no additive effect on the expression of Incw1 (Figure 1). This may be because the Incw1gene encodes 2 distinct transcripts, Incw1-S (small) and Incw1-L (large), which differ in size because the 3ꞌ untranslated region and 2 transcripts induced by sucrose and glucose differ in length (Cheng et al, 1999). The specific effects of ABA on the 2 transcripts are unknown.…”
Section: Discussionmentioning
confidence: 99%